Genetic variability of CYP3A4 in a heterogeneous Brazilian population from Maranhão - Monteiro, S. C. Moutinho (2016)
Inter-individual variability in drug metabolism may result in adverse drug responses. Pharmacogenetic studies have shown that polymorphisms in drug metabolizing enzymes may contribute to this variability. Among these enzymes, CYP3A4 is responsible for metabolizing over 50% of the clinically used drugs. The Brazilian population is composed of people with Native American, European, and African ancestries, and is therefore considered as one of the most intermixed populations in the world. A thorough knowledge of the genetic frequencies of CYP3A4 allelic variants is useful for the establishment of better pharmacological therapies; therefore, the aim of this study was to describe the polymorphic frequencies for CYP3A4 -392A>G (rs2740574) in a sample population from Maranhão, Brazil. Our results showed that 75.1, 21.9, and 3.0% of the individuals expressed the -392AA, -392AG, and -392GG genotypes, respectively. The -392A and -392G alleles were observed in 86.1 and 13.9% of the population, respectively. Our results reiterate the need for a better understanding of the variations in the genotype and allele frequencies of CYP3A4 -392A>G polymorphisms in various Brazilian regions, in order to elucidate the variability in drug response